Odpowiedź :
4(5y+)(1-5y)-5(1+4x)(1-4x)=80
(x-7)(2x-1)=nie wiem
(2a_1)(a+4)=2ado potegi 2 +7a-4
(x-7)(2x-1)=nie wiem
(2a_1)(a+4)=2ado potegi 2 +7a-4
4(5y+1)(1-5y)-5(4x+1)(1-4x) dla x= -1 i y= 0,1
4(5y+1)(1-5y)-5(4x+1)(1-4x)=
=4(1-25y²)-5(1-16x²)=
=4-100y²-5+80x²=
=80x²-100y²-1=
=80×1-100×0.1-1=
=80-1-1=
=78
a) (x+7)(2x-1)=2x²-x+14x-7=2x²+13x-7
b)(2a-1)(a+4)=2a²+8a-a-4=2a²+7a-4
c)(2a-1)(a+4)=2a²+8a-a-4=2a²+7a-4
To tyle, ja dziękuję i polecam się
4(5y+1)(1-5y)-5(4x+1)(1-4x)=
=4(1-25y²)-5(1-16x²)=
=4-100y²-5+80x²=
=80x²-100y²-1=
=80×1-100×0.1-1=
=80-1-1=
=78
a) (x+7)(2x-1)=2x²-x+14x-7=2x²+13x-7
b)(2a-1)(a+4)=2a²+8a-a-4=2a²+7a-4
c)(2a-1)(a+4)=2a²+8a-a-4=2a²+7a-4
To tyle, ja dziękuję i polecam się
4(5y+1)(1-5y)-5(4x+1)(1-4x) dla x=-1 y=0,1
4(0,5+1)(1-0,5)-5(-4+1)(1+4)=4*1,5*0,5-5*(-3)*5=3+75=78
a) (x+7)(2x-1)=2x²*13x-7
b)(2a-1)(a+4)=2a²+7a-4
c)(2a-1)(a+4)=2a²+7a-4
:)
4(0,5+1)(1-0,5)-5(-4+1)(1+4)=4*1,5*0,5-5*(-3)*5=3+75=78
a) (x+7)(2x-1)=2x²*13x-7
b)(2a-1)(a+4)=2a²+7a-4
c)(2a-1)(a+4)=2a²+7a-4
:)